Perspectives on the role of the state in economic development: Taking stock of the “Developmental State” after 35 years - Kyle, Jordan (International Food Policy Research Institute, 2017)
This review evaluates the role of the state in development, offering a new framework for understanding what capabilities states need to overcome different types of market failures. This framework is employed to understand the successes and failures of state-led development in Malaysia. The review addresses three key questions. First, what do we know about developmental states and why they emerged? Second, what have developmental states achieved? In answering this question, I look not only at growth but also at structural transformation, economic “upgrading,” equity, and human capability enhancement. In contrast to the idea of a single “East Asian model” of development, I find five distinct development trajectories. Third, how did developmental states utilize state structures to pursue development? To answer this final question, I examine in depth the history of state-led development in Malaysia—including agricultural, industrial, and social policies. This case study sheds light on what specific institutional and political capacities helped Malaysia to improve productivity in agriculture, expand the manufacturing sector, and reduce inequality. It also explores why Malaysia has been less successful in developing linkages with the export-based manufacturing sector.